(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In modern linguistics, paralinguistic means are recognized as an important component of human communication. Paralinguistics is the study of oral speech as a means of supplementing and enriching it with non-verbal, but meaningful means. Volume, intonation, body movements, facial expressions, pauses and other means ensure a wide range of information transmission in communication. Today, the possibilities of identifying, processing and analyzing paralinguistic information are expanding with the help of artificial intelligence, multimodal corpora, video analytics, audience monitoring systems and other technologies. This article sheds light on the use of modern methods in working with paralinguistic information, reveals the essence of paralinguistic methods and their types in modern information transmission, and reveals the effectiveness of these methods based on scientific analysis.